Browser-based demonstration of blockchain distributed ledger - Chu, Zhen Ting (2019)
Blockchain applications have expanded its influence beyond the field of cryptocurrencies into many other different areas of focus. Many industries have incorporated Blockchain technology into their business model to take advantage of the benefits of having a decentralised, immutable and transparent application. Though many people have heard of the term "Blockchain", there are still a handful of people uncertain of how Blockchain technology functions. Learning institution is identified as one of the leading areas where integration of beginner and intermediate Blockchain courses into the school curriculum have started. Hence, this report examines the different alternatives for interactive learning opportunities using Blockchain technology to educate the students on extensive Blockchain information. It will assists individuals to discover the fundamentals understanding of Blockchain information and develop their interest in it. The application, Cryptochain is developed in this project, which targets to enhance the learning of Blockchain information through the use of better visualization and interactive in class. This in return will reduce the time required for students to understand the fundamentals and provide the educator with additional time to focus on the more intermediate or advanced topics.